The Formation of the Legal Faculty and its Application - Mahmoud, Sayed; Mahmoud, Ahmed (Journal of Legal Sciences, 2023)
The sound legal thinking that reaches sound legal results is the basis of the legal faculty that is defined as: the faculty of the legal person to understand the legal language verbally and meaningfully and coexist in it and deal with it and realize and choose what words it can from it when needed during work and professional dealing, but this thinking does not have a methodology in specific and specific jurisprudence, as the faculty does not have a fixed size or a certain limit, but is flexible and expands It grows as its owner fills it with legal information and practical experience. The legal faculty has not been regulated by the legislator, in addition to the fact that the judiciary and jurisprudence have not dealt with this by expressing their jurisprudence in this context. Therefore, these problems oblige us to solve them to contribute to clarifying their assumptions and indicating their requirements, elements and components on the one hand, and then determine the field of application on the other hand, by following an analytical approach and a plan consisting of two sections: the first of which is the assumptions of the legal faculty and its requirements and the statement of its elements and components, and the second is the field of application to facts and law.